ESTUDIO DE GRADUADOS DE LA CARRERA DE MEDICINA HUMANA. UNIVERSIDAD NACIONAL DE LOJA 2003-2004 - UQUILLAS VALLEJO, SONIA (2010)
ESTUDIO DE GRADUADOS DE LA CARRERA DE MEDICINA HUMANA. UNIVERSIDAD NACIONAL DE LOJA 2003-2004